What Is the Appropriate Duration of High-Dose Atorvastatin Therapy Post-Acute Coronary Syndrome?. (December 2015) - Goriacko, Pavel; Andersen, Matthew; Fazylov, Roman; Plakogiannis, Roda
Purpose: To determine the optimal duration of high-intensity atorvastatin therapy post-acute coronary syndrome (ACS). Summary: A literature review was conducted using the MEDLINE database (1966-October 2013) and employing the search terms "atorvastatin OR statins AND myocardial infarction OR acute coronary syndromes." Clinical trials in the English language with available abstracts were used to identify potential data sources. Four major trials evaluating atorvastatin 80 mg daily after an ACS were identified. The duration of follow-up ranged from 16 weeks to a median of 4.9 years. High-dose atorvastatin regimens were associated with a reduction in coronary events but also with higher rates of drug discontinuation due to adverse reactions. The benefit of high-dose atorvastatin has been sustained for at least 5 years. Conclusion: After an ACS, high-dose atorvastatin should be continued for at least 5 years. High-dose atorvastatin demonstrated a reduction in coronary events but dose reductions and higher discontinuation rates were also noted.